2019
DOI: 10.3233/jad-190474
|View full text |Cite
|
Sign up to set email alerts
|

Midlife Hypertension and Alzheimer’s Disease: A Systematic Review and Meta-Analysis

Abstract: Background: Hypertension is an established risk factor for stroke and vascular dementia but recent meta-analyses examining the association between Alzheimer's disease (AD) and hypertension have found no significant association. These metaanalyses included short term studies starting in late life which may have obscured the real effect of midlife hypertension. Objective: To examine the association of AD with midlife hypertension, by including only studies with a sufficiently long follow up duration. Methods: Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 52 publications
5
90
0
1
Order By: Relevance
“…Smoking associates with increased risk of dementia, 24 , 27 and is likely mediated by cardiovascular pathology and the content of neurotoxins in cigarette smoke. 1 , 28 Midlife hypertension is consistently associated with increased risk of dementia 1 , 5 , 29 —an association we can confirm at least for men in the present study—and is suggested to be through increased risk of cerebrovascular disease and the metabolic syndrome. 1 Physical activity is inversely associated with risk of dementia, 1 , 5 , 30 an association mainly explained by cardiovascular risk factors.…”
Section: Discussionsupporting
confidence: 77%
“…Smoking associates with increased risk of dementia, 24 , 27 and is likely mediated by cardiovascular pathology and the content of neurotoxins in cigarette smoke. 1 , 28 Midlife hypertension is consistently associated with increased risk of dementia 1 , 5 , 29 —an association we can confirm at least for men in the present study—and is suggested to be through increased risk of cerebrovascular disease and the metabolic syndrome. 1 Physical activity is inversely associated with risk of dementia, 1 , 5 , 30 an association mainly explained by cardiovascular risk factors.…”
Section: Discussionsupporting
confidence: 77%
“…CI had higher SBP than CN in this study. A Meta-analysis showed a correlation between SBP and AD, meanwhile no correlation for DBP [25], which was consistent with our research. Our study found that CI had a higher PSQI score than CN, which represented a worse quality of sleep.…”
Section: Discussionsupporting
confidence: 92%
“…80 A recent metaanalysis studied this correlation in more depth and showed that, in particular, stage one (BP > 140 mm Hg/90 mm Hg (systolic/diastolic)) or two (BP > 160 mm Hg/95 mm Hg) systolic hypertension, but not diastolic hypertension (> 90 mm Hg distolic), was associated with more severe AD. 81 These cardiovascular risk factors are all associated with brain blood flow reductions and increased microemboli, 82 and it may be, in part, through these flow reductions that these cardiovascular risk factors influence AD progression. In addition, cardiovascular disease, such as coronary heart disease or small vessel disease, is associated with brain hypoperfusion (largest in watershed regions, including the basal ganglia, white matter, and hippocampus [83][84][85] ) and has been shown to increase the risk of developing MCI and dementia.…”
Section: Cerebral Blood Flow Reductions In Patients With Alzheimer's Diseasementioning
confidence: 99%